The Relationship between Pregnant Women's Knowledge Level of Exclusive Breastfeeding and Success in Breastfeeding at Birem Bayeun Health Center, Birem Bayeun District, East Aceh Regency, Aceh Province - Yusliana; Melya Efrianti; Dewi Yusra; Fitri Andri Yani; Rosmala Dewi (Journal Public Health and Clinical Science, 2026)
Exclusive breast milk is the best food for babies in the first six months of life because it contains complete nutrients and antibodies that can increase the baby's immunity. However, the coverage of exclusive breastfeeding has still not reached the expected target. One of the factors that affect the success of exclusive breastfeeding is the level of mother's knowledge about the benefits and importance of breastfeeding for the baby. To determine the relationship between the level of knowledge of mothers about exclusive breastfeeding and the success of breastfeeding in the working area of the Birem Bayeun Health Center, Birem Bayeun District, East Aceh Regency. This study is a quantitative research with an analytical approach using a cross sectional design. The population in this study is all mothers who have babies aged 0-6 months in the working area of the Birem Bayeun Health Center as many as 72 people. The sampling technique used the Slovin formula so that a sample of 42 respondents was obtained. Data collection was carried out using a questionnaire and analyzed using the Chi-Square statistical test with a 95% confidence level. Results: The results showed that most of the respondents had a good level of knowledge as many as 18 people (42.9%). Most mothers managed to give exclusive breastfeeding to their babies as many as 26 people (61.9%). The results of the Chi-Square test showed a p-value of 0.018 (p < 0.05). Conclusion: There was a significant relationship between the level of maternal knowledge about exclusive breastfeeding and the success of breastfeeding in the working area of the Birem Bayeun Health Center, Birem Bayeun District, East Aceh Regency. It is hoped that health workers can increase education and counseling to pregnant and breastfeeding women about the importance of exclusive breastfeeding.